Equilibrium properties of clusters in the harmonic superposition approximation - Calvo, F; Doye, J; Wales, D (2002)
The inherent structure approach, or superposition approach is used to calculate some physical and chemical properties of clusters in thermodynamic equilibrium, for both the classical and quantum regimes. In the harmonic approximation some simple analytical estimates are obtained for the average polarizability of metal clusters, and for the photoabsorption intensity of chromophore-doped van der Waals clusters. Comparison with Monte Carlo simulations reveals good agreement, which could be further improved using systematic corrections for anharmonic perturbations. © 2002 Elsevier Science B.V. All rights reserved.